PHARMACOGNOSTIC EVALUATION OF TOONA CILIATA BARK. - Ajay Gautam; Deenanath Jhade; Dheeraj Ahirwar; Manish Sujane; Ganesh N. Sharma (Wolters Kluwer Medknow Publications, 2010)
Pharmacognostic standardizations of powdered and anatomical sections of the Toona ciliata bark was carried out to determine its macro- and microscopical characters and also some of its quantitative standards. Externally bark are Grey to reddish-brown in colour when it is dry, 200 mm in length, 20 to 60 mm in width and 2 to 3 mm in thickness outer surface brown coloured, strong odour, bitter taste, rough and hard, double quill and curved curvature. The transverse section (T.S.) revealed the presences of periderm, cortex, Sclerides, medullary rays and phloem fiber. Physico-chemical evaluation includes ash values, extractive values and moisture content. These findings will be useful towards establishing pharmacognostic standards on identification, purity, quality and classification of the plant, which is gaining relevance in plant drug research.